Kedudukan Akta Notaris sebagai Alat Bukti dalam Sistem Pembuktian Perdata di Era Digitalisasi Hukum - Salsabila Zerlina Putri; Ery Agus Priyono (Journal of Creative Student Research, 2026)
This study examines the legal position of notarial deeds as evidentiary instruments within the civil proof system in the era of legal digitalization. The research is grounded in normative legal methodology, employing statutory and conceptual approaches to analyze the interaction between authentic deeds and electronic evidence. The findings indicate that notarial deeds retain their status as authentic evidence with perfect probative force under the Civil Code, yet their dominance is increasingly challenged by the recognition of electronic documents under the Information and Electronic Transactions Law. The expansion of evidentiary scope toward digital evidence has shifted the paradigm of civil proof from formalistic reliance on physical documents to technology-based validation emphasizing authenticity, integrity, and system reliability. This transformation creates normative tension and uncertainty regarding the hierarchy and relational status between notarial deeds and electronic evidence. The absence of an integrative framework within civil procedural law further complicates judicial assessment of evidentiary strength. The study highlights the urgency of reconstructing the civil proof system through regulatory harmonization and conceptual integration to ensure legal certainty, adaptability, and coherence in addressing evolving technological developments within the legal domain.